The influence of the board of directors’ characteristics on firm performance: evidence from Malaysian public listed companies - Abdulsamad, Abdulkader Omer; Wan Yusoff, Wan Fauziah; Lasyoud, Alhashmi Aboubaker (Virtus Interpress, 2018)
This paper aims to investigate the influence of board characteristics on firm performance. The four boards of directors’ characteristics that are of interest in this paper are: CEO duality, independent directors (ID), board size (BS) and board meeting (BM). Return on Assets (ROA) and Earnings per Share (EPS) are used as measurements for firm performance. Data were collected from secondary sources based on a purposively selected sample of 341 Malaysian Public Listed Companies throughout the period ranging from 2003 to 2013. The data were analyzed using the panel data regression model. Results of testing the influences between board characteristics and firm performance are found to be mixed. For example, board meetings showed weak and negative influences on firm performance while independent directors had weak and positive influences only on ROA. Based on the findings of this study, it has been observed that the present listing requirements, which aligned with the assumptions of agency theory, by the Malaysian Code on Corporate Governance (MCCG) and by the Bursa Malaysia requirements, might not be effective as expected in enhancing future firm performance.